No more crying about spilt milk - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Manual on the Use of the LP-system in Milk Handling and Preservation. Animal Production Service, FAO. 31 pp. ISBN 92 5 104254 3 $8.00 e 7.80